2010
DOI: 10.1161/hypertensionaha.109.146233
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Neurocardiac Training in Hypertension

Abstract: Abstract-It is not established whether behavioral interventions add benefit to pharmacological therapy for hypertension.We hypothesized that behavioral neurocardiac training (BNT) with heart rate variability biofeedback would reduce blood pressure further by modifying vagal heart rate modulation during reactivity and recovery from standardized cognitive tasks ("mental stress"). This randomized, controlled trial enrolled 65 patients with uncomplicated hypertension to BNT or active control (autogenic relaxation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 26 publications
2
45
0
3
Order By: Relevance
“…This is partially correct and (surprisingly) it is more consistent with details of our 2005 trial [3]. In contrast, markers of vagal heart rate modulation in our 2010 trial [4] included not only HF power, but baroreflex sensitivity and RR interval as well. Indeed, a compelling feature of our secondary analysis of that trial is that we observed an inverse association between change in each of these markers of vagal heart rate modulation and change in hsCRP-as the resting baseline measures were compared before versus after an 8-week period of behavioural intervention.…”
Section: Dear Sirsupporting
confidence: 83%
“…This is partially correct and (surprisingly) it is more consistent with details of our 2005 trial [3]. In contrast, markers of vagal heart rate modulation in our 2010 trial [4] included not only HF power, but baroreflex sensitivity and RR interval as well. Indeed, a compelling feature of our secondary analysis of that trial is that we observed an inverse association between change in each of these markers of vagal heart rate modulation and change in hsCRP-as the resting baseline measures were compared before versus after an 8-week period of behavioural intervention.…”
Section: Dear Sirsupporting
confidence: 83%
“…52 Training in behavioral neurocardiac training and in the control was supplemented by 20-minute audiotaped exercises for daily home practice. Behavioral neurocardiac training reduced daytime and 24-hour systolic BP levels (−2.4±0.9 mm Hg, P=0.009, and −2.1±0.9 mm Hg, P=0.03, respectively).…”
Section: Recent Trialsmentioning
confidence: 99%
“…51,52 It is plausible that some techniques may be more effective than others 52 ; however, a paucity of data precludes making recommendations for implementing a specific methodology to treat high BP in clinical practice. On the other hand, no significant health risks were reported among the trials.…”
Section: Summary and Clinical Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] It is shown that the application of HRVB helps to normalizing BP, increasing vagal reserve of autonomic regulation of cardiac activity. [13,14] Realization of the biofeedback effect is possible with the optimal functioning of the higher nervous activity mechanisms (motivation, memory, emotional and positive reinforcement) and cortical-visceral relations from the cardiovascular centers in the brain to the cardiac conduction system.…”
mentioning
confidence: 99%